The Exploring The Epistemological Basis of Ushul Fiqh (Priority Fiqh By Yusuf Al-Qardawi): English - Turmudzi, Khoiru; Ramadhani, Noni; Rusdian, Alvin; Karim, Nauval; Maulida, Kartika; Mukti, Ahsan (Indonesian Journal Publisher, 2025)
This article explores the epistemological foundations of Ushul Fiqh, particularly focusing on the concept of Priority Fiqh as articulated by Yusuf Al-Qardawi. In the contemporary context, Muslims face numerous challenges in prioritizing religious obligations and ethical considerations amidst a rapidly changing world. Al-Qardawi's approach emphasizes the need for a systematic framework that aids in discerning the priority of Allah's commandments, thoughts, and charitable actions. Through a qualitative analysis of Al-Qardawi's writings and relevant literature, this study elucidates the methodologies he proposes for addressing the complexities of modern Islamic jurisprudence. The findings highlight the significance of prioritization in Fiqh as a means to navigate moral dilemmas and enhance the application of Islamic principles in daily life. Ultimately, this article contributes to the discourse on Islamic legal theory by advocating for a renewed understanding of Fiqh that is responsive to contemporary needs while remaining rooted in traditional scholarship.